Generation of carbamoyl phosphate synthetase 1 reporter cell lines for the assessment of ammonia metabolism. Issue 12 (30th May 2017) - Wang, Yi; Chang, Le; Zhai, Jiahui; Wu, Qiao; Wang, Donggen; Wang, Yunfang
Abstract: Both primary hepatocytes and stem cells‐derived hepatocyte‐like cells (HLCs) are major sources for bioartificial liver (BAL). Maintenance of hepatocellular functions and induction of functional maturity of HLCs are critical for BAL's support effect. It remains difficult to assess and improve detoxification functions inherent to hepatocytes, including ammonia clearance. Here, we aim to assess ammonia metabolism and identify ammonia detoxification enhancer by developing an imaging strategy. In hepatoma cell line HepG2, and immortalized hepatic cell line LO2, carbamoyl phosphate synthetase 1 (CPS1) gene, the first enzyme of ammonia‐eliminating urea cycle, was labelled with fluorescence protein via CRISPR/Cas9 system. With the reporter‐based screening approach, cellular detoxification enhancers were selected among a collection of 182 small molecules. In both CPS1 reporter cell lines, the fluorescence intensity is positively correlated with cellular CPS1 mRNA expression, ammonia elimination and secreted urea, and reflected ammonia detoxification in a dose‐dependent manner. Surprisingly, high‐level CPS1 reporter clones also reserved many other critical hepatocellular functions, for example albumin secretion and cytochrome 450 metabolic functions. Sodium phenylbutyrate and resveratrol were identified to enhance metabolism‐related gene expression and liver‐enriched transcription factors C/EBPα, HNF4α. In conclusion, the CPS1‐reporter system provides an economic and effective platform for assessment of cellular metabolic function and high‐throughput identification of chemical compounds that improve detoxification activities in hepatic lineage cells.